Double Jeopardy-Analyzing the Combined Effect of Age and Gender Stereotype Threat on Older Workers - Manzi, Claudia; Sorgente, Angela; Reverberi, Eleonora; Tagliabue, Semira; Gorli, Mara (Frontiers in Psychology, 2021)
In this study we aim to analyze the combined effect of age-based stereotype threat and gender stereotype threat on work identity processes (and in particular on authenticity and organizational identification) and on work performance (self-rating performance). The research utilizes an ample sample of over fifty-year-old workers from diverse organizations in Italy. Using a person-centered approach four clusters of workers were identified: low in both age-based stereotype threat and gender discrimination (N= 4689), high in gender discrimination and low in age-based stereotype threat (N=1735), high in age-based stereotype threat and low in gender discrimination (N=2013) and high in both gender discrimination and age-based stereotype threat (N=758). Gender was significantly associated with these clusters and women were more frequently present in those groups with high gender stereotype threat. ANOVA results show that workers in the last two clusters score significantly lower in authenticity, organizational identification and self-rate performance. All in all, if ageism is undoubtedly problematic for older workers’ identity processes, ageism and gender-stereotypes represent a double risk for women over fifty in the workplace. The analysis of the results can be beneficial both for the theoretical advancement and for the practical insights offered in the organizational and management field, where new policies of HR management can be elaborated, in order to value and to improve the workers experience.